2003
DOI: 10.1080/00914030304903
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic effect of hydroxyapatite types on the polymerization of acrylic bone cements

Abstract: The effect of type and amount of hydroxyapatite on the setting kinetics of an experimental bone cement based on poly(methyl methacrylate-co-styrene) was studied. The average molecular weights of the polymeric beads synthesized were determined by SEC and the average particle size was determined by Optical Microscopy. Three types of hydroxyapatites were synthesized in the laboratory and then characterized by ICP, FTIR and X-ray diffraction. To obtain more compatible fillers, the hydroxyapatites were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
(13 reference statements)
2
24
0
1
Order By: Relevance
“…A decrease in peak temperature and slower reaction has also been reported when using HA as a filler. [8] Because a lower temperature peak may cause less damage to surrounding tissues, lower reaction rates are convenient for long term fixation of an implant. The slower reactions and peak temperatures can be explained in terms of filler higher thermal conductivity (2.4 $ 3.0 W/m Á K) compared to that of PMMA (0.46 W/mK).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in peak temperature and slower reaction has also been reported when using HA as a filler. [8] Because a lower temperature peak may cause less damage to surrounding tissues, lower reaction rates are convenient for long term fixation of an implant. The slower reactions and peak temperatures can be explained in terms of filler higher thermal conductivity (2.4 $ 3.0 W/m Á K) compared to that of PMMA (0.46 W/mK).…”
Section: Resultsmentioning
confidence: 99%
“…[1] Because almost 98 wt% of the total calcium in human organisms is present in the osseous structure as hydroxyapatite crystals C 10 (PO 4 ) 6 (OH) 2 , calcium phosphate Ca 3 (PO 4 ) 2 , and calcium carbonate CaCO 3 , [5] in an attempt to increase biocompatibility and to promote bone growth around an implant, several studies incorporating hydroxyapatite (HA) and calcium phosphate have been reported. [1,[6][7][8] The presence of bioactive particles, besides modifying mechanical properties of the bone cement, [8,9] also affects curing characteristics. Morejó n et al, reported that when using HA as filler in a poly (methyl methacrylate-co-styrene) bone cement, lower curing temperature peaks than for the unfilled cement were obtained.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of each of these properties has been discussed in the literature. Thus, (1) FL is important in terms of the fact that fatigue of the cement mantle has been implicated in aseptic loosening of cemented TJRs, which is the leading cause of their failure [17] (thus, high FL is desirable); (2) K IC is an index of the damage tolerance of the cement (that is, its ability to resist brittle fracture in the presence of crack(s) in it) [18] (thus, high K IC is desirable); (3) k 0 is related to the long-term in vivo stability of a cemented arthroplasty [19] (low k 0 is desirable); and (4) D is an index of the potential for the plasticizing influence of PBS on the cement's properties; thus, there are reports of this influence in the case of, for example, ultimate tensile strength [20], glass transition temperature [21], and elastic modulus [22]. There is disagreement on whether such reductions are detrimental to the in situ life of a cemented TJR; for example, Lewis et al [22] suggested that high D adversely affects the dimensional stability of the cement whereas Kuhn et al [21] suggested that lowered modulus may be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…[8] Se conoce que los altos calores de polimerización pueden causar necrosis del tejido en los alrededores de la prótesis y además puede afectar severamente la durabilidad del implante debido a que induce la reabsorción del tejido óseo y produce aflojamiento de la prótesis. [9] El estudio de la bioactividad in vitro es un ensayo importante a valorar en este tipo de biomateriales. [8] Su determinación se fundamentan en el hecho de que en los materiales cerámicos que se enlazan directamente al hueso se ha podido demostrar que las primeras etapas del mecanismo de enlace pueden simularse en un medio inorgánico, sin presencia de células, siempre y cuando dicho medio contenga los iones necesarios para que el material pueda desarrollar una nueva fase tipo carbonato-hidroxiapatita (CHA) en su superficie.…”
Section: Caracterización Mecánicaunclassified